Analysis of The Implementation of Organic Waste Management Policy - Zaini, Zaman; Sukmawati, Sonia; Tuswoyo, Tuswoyo; Junaidi, Ahmad (Journal Socio Humanities Review, 2023)
The background of this research isthephenomenonoftheuniquemanagementoforganicwaste. The activityiscarriedby "Woro-woro" andmodifyingthegarbagecarttoinclude 3 typesofgarbagebins, speakers,andloudspeakersonthegarbagecart.Thisprovesthat RW 017 hasimplementedGovernorRegulation 77 of 2020. Thismethodisdifferentfromotherregionsthatyethavetheknowledgeandawarenesstoproperlymanagewaste, especiallyorganicwaste.The objectivesofthisstudywere1) To analyzetheimplementationofthepolicy in managingorganicwastein RW 017 Pegangsaan Dua Kelapa Gading 2) To analyzetheobstaclesthatinfluencehowlocalgovernmentpolicy in managingorganicwaste inRW017PegangsaanDuaKelapaGading3)Toanalyzeeffortstoovercomeobstaclesthatoccurinhowlocalgovernmentpolicyinmanagingorganicwaste in RW017 Pegangsaan Dua Kelapa Gading.Thisresearchmethodusedqualitativeresearchmethodusingdatacollectiontechniquesofobservation, documentation, andinterviews. Thedataanalysistechniquesusedweredatareductionanalysis,datapresentation,anddataverification.Theresultsoftheresearchshowedthattheimplementationofthepolicyimplemented in RW 017 PegangsaanDua,namelytheGubernatorialRegulationnumber77/2020onWasteManagement in theScopeofcommunity unit, where RW 017 focusesonorganicwastemanagementissaidtobesuccessful. By segregatingwastefromitssourceandmanagingwaste, theamountofwastegeneratedisreduced. The obstacles in thewastemanagement in RW 017 are thelackofinsulationofgarbagebinsandtheunfavorableweather. The effortstoovercometheseobstacles are byprovidingwastecompartmentaccordingtothetypeofwasteandbycarryingoutdoublewastetransportation.